Pengaruh Quenching Terhadap Beban Impak Pada Besi Cor Kelabu - Arafat, Yasir, Agus Yulianto, ST., MT (2017)
This study aims to determine the effect of Quenching on gray cast iron to impact loads. This study uses sand molds with cylindrical wood pattern. The methodology of this research is done with cast iron melting in induction furnace and then is poured in sand molds for making gray cast iron specimen. Tests in liquid form gray cast iron using test equipment CE Meter and the specimen gray cast iron Before the test process is carried out heat treatments Qhuenching reached 7500C in an interval of 4 hours, then tested the composition and in the impact test as well as in hardness and micro photograph to to know the difference atara in heat treatments and without heat treatment Quenching Quenching. Results of the research is a chart obtained from CE Meter shows the temperature 1278.0 ° C during tapping early in the cast in the mold at the start on the chart that reads CE Meter decrease the temperature, the liquid temperature of 1154.2 ° C shape is still liquid to a temperature solid 1112.6 ° C so that the obtained value CEL = 4.10%; C = 3.43%; and SI = 2.28% where the metal solid starts but is still red up to a temperature of 1060 ° C, while the test results of the chemical composition in the form of solid or solid among others: Fe 93.57%; C 3.43%; 1.86% Si and other elements under 1%. The impact test results show through heat treatment qhuenching get results Impact Value 0.03 J / mm and without heat tratment qhuenching impact value of 0.02 J / mm. The test results of micro structures are shaped graphite eutectic. Based on these data we can conclude that through a process of heat treatment may affect the results kekerasandan qhunching also testing impack greater.